1993
DOI: 10.1152/jn.1993.70.4.1307
|View full text |Cite
|
Sign up to set email alerts
|

Late expiratory inhibition of stage 2 expiratory neurons in the cat--a correlate of expiratory termination

Abstract: 1. Intracellular recordings were made from stage 2 expiratory bulbospinal neurons (E2Ns) in the caudal part of the ventral respiratory group in pentobarbitone-anesthetized cats, to characterize changes in neuronal input resistance (Rn) and synaptic inhibition occurring at the time of the expiratory-inspiratory phase transition of the respiratory cycle. 2. Rn was maximal between 30-90% of stage 2 expiration, but decreased significantly during the last 10% of stage 2 expiration. Mean normalized Rn for 60-90% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…7). It was suggested that they play a role in the transition between expiration and inspiration (6,28,51). Lengthening of the interval between the biphasic discharges of type 2 neurons is consistent with lengthening of inspiration and expiration by opioids.…”
Section: Discussionmentioning
confidence: 68%
“…7). It was suggested that they play a role in the transition between expiration and inspiration (6,28,51). Lengthening of the interval between the biphasic discharges of type 2 neurons is consistent with lengthening of inspiration and expiration by opioids.…”
Section: Discussionmentioning
confidence: 68%
“…Originally described by Cohen (1969), pre-inspiratory (PreI) neurones have recently been reported to play critical roles in both the initiation of inspiration (Smith, Ellenberger, Ballanyi, Richter & Feldman, 1991;Smith, Funk, Johnson & Feldman, 1995) and termination of expiration (Klages, Bellingham & Richter, 1993;Schwarzacher, Smith & Richter, 1995). Thus, the present study tests the hypothesis that PreI neurones inhibit PI neurones during PCF-induced PI apnoea thereby promoting the recommencement of inspiration.…”
mentioning
confidence: 78%
“…PreI neurones may terminate expiration since the onset of the inspiratory-related inhibition of E neurones coincides with the pre-inspiratory period (Klages et al 1993;Paton, 1996b). On this basis, it was proposed that PreI neurones participate in an expiratory off-switch mechanism (Cohen, 1969;Klages et al 1993).…”
Section: Putative Roles Of Prei Neurones In the Respiratory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In a specific type of respiratory neuron this is reflected by an alternation of excitatory synaptic drive mediated by glutamate and synaptic inhibition mediated by GABA and glycine (Schmid, Foutz & Denavit-Saubie, 1996). Synaptic inhibition results in reversible and irreversible switching off of phasic activities and shaping of neuronal discharge patterns (Richter, Camerer, Meesmann & R ohrig, 1979;Richter, 1982;Ballantyne & Richter, 1986; Remmers, Richter, Ballantyne, Bainton & Klein, 1986; Anders, Ballantyne, Bischoff, Lalley & Richter, 1991;Haji, Takeda & Remmers, 1992;Klages, Bellingham & Richter, 1993;Schmid et al 1996). Blockade of GABAergic and glycinergic mechanisms by systemic or local administration of receptor antagonists greatly disturbs rhythmic respiratory functions when studied under in vivo conditions (Hayashi & Lipsky, 1992) or under in vitro conditions in slice preparations that contain more rostral medullary and pontine structures (Paton, Ramirez & Richter, 1994;Paton & Richter, 1995).…”
mentioning
confidence: 99%